Arc erosion resistance of CuCrMo films deposited via magnetron sputtering - Li Kai; Miao Xiaojun; Qian Dan; Yulou Li; Meng Yu; Pang Yajuan; Yang Bo; Li Yanhuai; Hao Liucheng; Fan Yanyan; Song Zhongxiao (Materials Research Express, 2021)
Copper-chromium (CuCr) alloys are widely used as electrical contact materials, and their arc erosion resistance can be improved by reducing the sizes of the Cu and Cr phases or by adding Mo. In this study, supersaturation solid solutions of CuCr and CuCrMo films were prepared via magnetron sputtering. After annealing at 773 K, the CuCr and CuCrMo films are composed of a small Cu-rich face-centred cubic phase and a Cr-rich body-centred cubic phase. Meanwhile, the addition of Mo reduces the diffusion rate during annealing. The lattice distortion of the CuCrMo thin film exceeds that of the CuCr film, and the elastic modulus and hardness increase. Compared with those of the CuCr film, the erosion area of the CuCrMo film is larger, and the depth of the erosion pit is lower. The arc erosion experiment proved that CuCrMo films exhibit satisfactory arc erosion resistance.